2014
DOI: 10.2527/jas.2014-7710
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diet on microRNA expression in ovine subcutaneous and visceral adipose tissues1

Abstract: Knowledge of the molecular mechanisms that regulate ovine adipogenesis is very limited. MicroRNAs (miRNA) have been reported as one of the regulatory mechanisms of adipogenesis. This study aimed to compare the expression of miRNA related to ovine adipogenesis in different adipose depots and to investigate whether their expression is affected by dietary fatty acid composition. We also investigated the role of miRNA in adipogenic gene regulation. Subcutaneous and visceral adipose tissue samples were collected at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 44 publications
2
23
1
Order By: Relevance
“…(2012) and Meale et al . (2014) have also reported that these miRNAs regulate lipogenesis and fat deposition in other animals3637. Taken together, the present study indicates that the higher intramuscular fat level in Wagyu cattle may be partially attributed to these 3 highly expressed miRNAs.…”
Section: Discussionsupporting
confidence: 74%
“…(2012) and Meale et al . (2014) have also reported that these miRNAs regulate lipogenesis and fat deposition in other animals3637. Taken together, the present study indicates that the higher intramuscular fat level in Wagyu cattle may be partially attributed to these 3 highly expressed miRNAs.…”
Section: Discussionsupporting
confidence: 74%
“…In lambs, miR‐136 was differentially expressed in subcutaneous adipose tissue compared with perirenal fat (Meale et al . ). Guo et al .…”
Section: Discussionmentioning
confidence: 97%
“…It has been demonstrated that diet and supplementary nutrients affect miRNA expression in adipose tissues of mice [1416], sheep [17] and cattle [18]. However, miRNAs in circulation and skeletal muscle have poorly understood in farm animals thus far.…”
Section: Discussionmentioning
confidence: 99%
“…Besides skeletal muscle, transcriptomic miRNA analyses in mammalian adipose tissue have unveiled their roles in fat accumulation. The relevance of miRNAs has also been pronounced in subcutaneous and/or visceral fat accumulation in response to growth and dietary nutrition in mice [1416], sheep [17], and cattle [18]. When primary cultured porcine adipocytes are exposed to miR-130b-enriched micro-vesicles, peroxisome proliferator-activated receptor γ ( PPARG ) expression is downregulated [19].…”
Section: Introductionmentioning
confidence: 99%